What Are the Rates and Trends of Women Authors in Three High-impact Orthopaedic Journals from 2006-2017?. Issue 7 (July 2020) - Hiller, Kathryn P.; Boulos, Alexandre; Tran, Megan M.; Cruz, Aristides I.
Abstract: Background: The gender gap among authors publishing research in journals is narrowing in general medicine and various medical and surgical subspecialties. However, little is known regarding the gender gap among authors publishing research in orthopaedic journals. Questions/purposes: (1) What is the proportion of women first and last authors of original research articles in three high-impact orthopaedic journals from 2006 to 2017? (2) What is the proportion women first authors of original research by orthopaedic subspecialty from 2006 to 2017? Methods: A sample of original research publications from the even numbered months of issues of Clinical Orthopaedics and Related Research ® (CORR®), the Journal of Bone and Joint Surgery, American volume (JBJS), and the American Journal of Sports Medicine (AJSM) were examined from 2006 to 2017. These journals were selected because of their clinical relevance, target audience, and relatively high impact factors. Over the studied period, a single author extracted and reviewed pertinent data, including the gender of the first and last authors and the primary subspecialty of the research article. The senior author refereed disputes regarding the primary subspecialty of each included article. The proportion of women first and last authors in each journal was compared between 2006 to 2017 using chi-square analysis. The proportion of women first authors according to orthopaedic subspecialty in which an article primarily focused its study was also compared between 2006 to 2017 using chi-square analysis. Results: Data were collected from 6292 articles, 13% (800) of which were first-authored by women and 10% (604) of which were last-authored by women. From 2006 to 2017, the overall percentage of women first authors in the examined journals increased (from 11% in 2006 to 17% in 2017; odds ratio 1.6563 [95 % CI 1.4945 to 1.8356]; p < 0.001). Overall across the period studied, the percentage of women first authors in JBJS was 14% while 12% of first authors in CORR and AJSM were women. Regarding subspecialty, the percentage of women first authorship ranged from 9% in the shoulder subspecialty to 21% in pediatric orthopaedics across all three journals. Conclusions: There has been an increase in the percentage of women first authors in articles published in three high-impact orthopaedic journals from 2006 to 2017. This observed increase is encouraging in terms of promoting gender diversity in orthopaedics and may be reflective of a modest increase in the number of women entering the orthopaedic workforce. Clinical Relevance: Between 2006 and 2017, the overall number of women first authors in CORR, JBJS, and AJSM modestly increased. This may suggest a nascent narrowing of the gender gap in orthopaedics. Although this is a welcome finding in terms of promoting and encouraging gender diversity in this man-dominated field, the overall percentage of women authorship remains modest, at best. Future investigations should examine whether the modest increase in women first authorship over time found in this study translates into an increased percentage of senior/last authorship in the future, as this may have implications for women orthopaedic workforce retention.